Spatial variations and potential risks of heavy metals in sediments, seawater, and marine organisms of Yuhuan coastal area, China - Zhang, Shuijun; Dong, Chao; Wang, Jianqiang; Zheng, Min; Chen, Xuanbo; Zhou, Yubo; Yang, Jiaojiao; Mao, Xiaohui (Frontiers in Marine Science, 2025)
Heavy metal pollution in coastal ecosystems poses significant ecological and health risks, yet comprehensive multi-compartment assessments in rapidly industrializing regions like Yuhuan remain scarce. To assess the heavy metal pollution status and potential risks in the coastal area of Yuhuan, this study collected 30 surface seawater samples, 16 surface sediment samples, and multiple marine organism samples in 2023. The concentrations and spatial distribution characteristics of seven heavy metals were analyzed. Multiple indices, including the geo-accumulation index, potential ecological risk index, and bioaccumulation factor, along with principal component analysis, were applied to assess ecological risks and identify pollution sources. The results indicated that heavy metal concentrations in sediments, seawater, and organisms all complied with China’s Class I marine environmental quality standards. Mercury posed a moderate ecological risk in sediments (mean Eri=41.08) and was the dominant contributor to regional ecological risk (51.80%), though the overall ecological risk level of the area remained low (mean RI = 79.31). The pollution load index ranged from 0.003 to 0.09 (mean = 0.04), confirming minimal anthropogenic influence. Marine organisms exhibited a stronger capacity for bioaccumulation of metals from the water column than from sediments, with crustaceans accumulating higher metal levels than fish. PCA revealed that heavy metals in sediments primarily originated from natural processes, agricultural activities, and localized anthropogenic emissions, while those in seawater were mainly associated with industrial wastewater and port activities. This study provides a scientific basis for environmental management, pollution control, and the sustainable development of aquaculture in the Yuhuan coastal area.